Satellite Remote Sensing of Drinking Water Intakes in Lake Erie for Cyanobacteria Population Using Two MODIS-Based Indicators as a Potential Tool for Toxin Tracking - Zhang, Feng; Hu, Chenlin; Shum, C. K.; Liang, Song; Lee, Jiyoung (Frontiers in Marine Science, 2017)
The growth of toxic Cyanobacterium, Microcystis aeruginosa, and the production of toxins, microcystins, pose serious concerns for the ecological health of lakes, such as western Lake Erie. The toxins are also significant health hazards and could contaminate tap water when sufficient and effective water treatment fails. In this study, water from the intakes of two water treatment plants along Lake Erie (Toledo and Painesville) were collected and examined for microcystins concentration (μg/L) and M. aeruginosa abundance (gene copies/mL) in concert with the performance of satellite-based cyanobacteria bloom indicators, chlorophyll-a and Cyanobacteria Index, a spectral shape index for monitoring the severity of cyanobacterial blooms from the Moderate Resolution Imaging Spectroradiometer (MODIS) from May to October in 2013. Good correlations were observed between toxic M. aeruginosa, microcystins, and MODIS-retrieved bloom indicators for the Toledo water plant intake, where blooms were much more severe with higher chlorophyll-a, phycocyanin and microcystins, but not for the Painesville water plant intake in central Lake Erie where the blooms were less severe. The Spearman's correlation (0.815) suggested a high correlation between the level of microcystins and MODIS-retrieved chlorophyll-a concentration for the Toledo intake point in western Lake Erie. Both total and toxic Microcystis abundance showed a significant positive correlation with MODIS-retrieved chlorophyll-a for the Toledo water intake, as well as the two locations combined. This finding demonstrates the potential utility of satellite remote sensing for detection and monitoring of cyanobacterial blooms, and the method's potential use as an early warning system as a means of preventing human exposure to bloom-impacted waters.